Behavioural ecology of urban Greylag Geese Anser anser – natural selection in the contemporary European city environment - Woog, Friederike (Wildfowl, 2025)
The behavioural ecology of urban Greylag Geese Anser anser was reviewed in relation to selective forces or bottlenecks – such as habitat, food availability, predators, disturbance, hunting, diseases and parasites, nest sites and brood rearing areas, and competition with other species – which may act on geese in the contemporary European city environment. Special consideration was given to behavioural changes during winter and moult. Studies to date indicate that urban geese have developed survival and reproduction strategies which sometimes differ from those of geese in other habitats. For instance, they must adapt to a more built-up environment, as additional mortality may arise from collisions caused by flying within confined urban spaces. They are also exposed to urbanised native, introduced and “domestic” predators, such as dogs, to which they show size-related escape responses. Most urban geese adapt to human disturbances, adjusting the intensity of their behavioural response to the perceived danger. Like their rural counterparts, urban geese are also highly selective in their choice of food plants and feeding habitat, although supplementary feeding by people may induce a change in behaviour. There was no evidence that disease or parasite loads are higher for geese in urban than in rural areas. Urban Greylag Geese use a broader range of physical structures for nesting in urban than in rural areas, with some also adopting colonial nesting. Some families moved to new brood-rearing areas immediately post-hatching, elevating reproductive success. Competition with other species was evident at some sites, with Greylag Goose breeding success being inversely related to the local abundance of Egyptian Goose Alopochen aegyptiaca breeding pairs. Although wintry conditions with snow and ice cover may limit food availability and frozen lakes may hinder the ability of largely sedentary urban geese to escape from predators, they appear able to cope with prolonged periods of cold. Urban geese have also demonstrated resilience during their flightless wing moult period. It is unlikely that urban goose populations will grow indefinitely, as density-dependent processes will lead to a stabilisation of the numbers which occur within the boundaries of a given city, although the geese may disperse into surrounding rural areas.